The impact of tropical storms on international trade: Evidence from Eastern Caribbean Small Island Developing States - Preeya Mohan (Inter-American Development Bank (IDB), 2023)
Eastern Caribbean Small Island Developing States (SIDS) have a high dependence on international trade for income, employment and poverty reduction given their extreme openness, small market size, narrow range of resources and productive capabilities and specialized economic structures, making them vulnerable to external shocks, the most frequent being tropical storms. The objective of this paper is to investigate the impact of tropical storms on international trade for eight Eastern Caribbean SIDS over the period 2000-2019, as well as the mediating role of the Real Effective Exchange Rate (REER). The results indicate that hurricanes have a more long-term impact on exports, reducing exports of goods by 20 percent in the month of a strike and up to three months thereafter, while the impact on imports was just as severe but more immediate, reducing imports of goods by 11 percent in the month of a strike. The mediation analysis suggests that the REER plays no mediating role in explaining the impact of tropical storm damage on exports and imports in the region.
Keywords: F1; F4; Q54; Q56; 330; Natural disasters; Hurricanes; International trade; Small IslandDeveloping States; Caribbean